2004
DOI: 10.1038/emm.2004.26
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human cerebral cortex in epileptic patients

Abstract: Abbreviations: 2-DE, 2-dimensional electrophoresis; ESI-Q-TOF, electrospray ionization quadupole time of flight; GPDH, Glycerol phosphate dehydrogenase; GPX, glutathione peroxidase; MALDI-TOF, matrix-assisted laser desorption/ionization-time-of flight; SOD, superoxide dismutase A bstractEpilepsy affects m ore than 0.5% of the w orld population and is know n to be associated w ith a large genetic com ponent eliciting an electrical hyperexcitability in the central nervous system . However, its pathogenic m echan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 16 publications
0
32
0
1
Order By: Relevance
“…Over the years, many theories of aging have been proposed in the field of aging research, but none of these theories are clearly testified yet. Therefore, it has been recently suggested that proteomics could offer great potential for molecular studies of biological aging and medicine (Dierick et al, 2002;Seong et al, 2002;Schoneich, 2003;Eun et al, 2004). As shown in Figure 3, no difference in calnexin level with aging was detected by Western blotting.…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…Over the years, many theories of aging have been proposed in the field of aging research, but none of these theories are clearly testified yet. Therefore, it has been recently suggested that proteomics could offer great potential for molecular studies of biological aging and medicine (Dierick et al, 2002;Seong et al, 2002;Schoneich, 2003;Eun et al, 2004). As shown in Figure 3, no difference in calnexin level with aging was detected by Western blotting.…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…Proteomic technologies and DNA microarray are providing the tools needed to discover and identify biomarkers associated with diverse diseases and biological processes (Hanash, 2003;Eun et al, 2004;Yao et al, 2005). NNMT was one of the potential tumor biomarkers identified recently by those technologies, in which NNMT in both mRNA and protein levels was found over-expressed in a wide range of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…During electrographic seizures and sustained depolarization, the elevated intracellular Ca ++ can result in both pathological and protective changes in the cellular protein composition of neurons or glial cells. These changes in the cellular proteom are under intense investigation in epilepsy research (Eun et al, 2004;Greene et al, 2007;Jiang et al, 2007;Junker et al, 2005;Ryu et al, 2007;Yang et al, 2006). Some of the available results emphasize the role of cytoskeletal impairment and cytoskeletal rearrangement in epilepsy (Greene et al, 2007;Ryu et al, 2007;Yang et al, 2006).…”
Section: Potential Of the 4-ap In Epilepsy Researchmentioning
confidence: 99%